The Impact of Corporate Governance on Capital Structure, Investment Opportunity Set, and Bank Performance: The Role of Credit Risk as a Moderating Variable - Nuraeni Nuraeni; M. Saifi; Nila Firdausi Nuzula; Cacik Rut Damayanti (Cita Konsultindo Research Center, 2024)
This research aims to examine the influence of corporate governance on capital structure, investment opportunity set and bank performance which is moderated by credit risk. This article attempts to fill the gap in research on the role of credit risk as a moderating variable between the influence of corporate governance on bank performance, the role of credit risk as a moderating variable between the influence of capital structure on bank performance, the role of credit risk as a moderating variable between the influence of investment opportunity set on bank performance in banking companies listed on the Indonesian Stock Exchange. The sampling method used was the judgment sampling technique. From 42 banking companies that had gone public on the Indonesian stock exchange, 20 banking companies were selected as research samples. The secondary data obtained was processed using warpPLS 7.0 software. The research results show that all the hypotheses proposed have a significant effect. Meanwhile, credit risk significantly strengthens the influence of corporate governance on bank performance, and credit risk significantly weakens the influence of capital structure on bank performance, and credit risk significantly strengthens the influence of investment opportunity set on bank performance in banking companies listed on the Indonesian Stock Exchange. The implication is that banking companies listed on the Indonesian Stock Exchange are expected to have bank performance through corporate governance, capital structure and investment opportunity set and be strengthened by credit risk.